Pharmacogenomics of Prostaglandin and Leukotriene Receptors - Cornejo-García, José A.; Perkins, James R.; Jurado-Escobar, Raquel; García-Martín, Elena; Agúndez, José A.; Viguera, Enrique; Pérez-Sánchez, Natalia; Blanca-López, Natalia (Frontiers in Pharmacology, 2016)
Individual genetic background together with environmental effects are thought to be behind many human complex diseases. A number of genetic variants, mainly single nucleotide polymorphisms (SNPs), have been shown to be associated with various pathological and inflammatory conditions, representing potential therapeutic targets. Prostaglandins (PTGs) and leukotrienes (LTs) are eicosanoids derived from arachidonic acid and related polyunsaturated fatty acids that participate in both normal homeostasis and inflammatory conditions. These bioactive lipid mediators are synthesised through two major multistep enzymatic pathways: PTGs by cyclooxygenase and LTs by 5-lipoxygenase. The main physiological effects of PTGs include vasodilation and vascular leakage (PTGE2); mast cell maturation, eosinophil recruitment and allergic responses (PTGD2); vascular and respiratory smooth muscle contraction (PTGF2), and inhibition of platelet aggregation (PTGI2). LTB4 is mainly involved in neutrophil recruitment, vascular leakage, and epithelial barrier function, whereas cysteinyl LTs (CysLTs) (LTC4, LTD4 and LTE4) induce bronchoconstriction and neutrophil extravasation, and also participate in vascular leakage. PTGs and LTs exert their biological functions by binding to cognate receptors, which belong to the seven transmembrane, G protein-coupled receptor superfamily. SNPs in genes encoding these receptors may influence their functionality and have a role in disease susceptibility and drug treatment response. In this review we summarize SNPs in PTGs and LTs receptors and their relevance in human diseases. We also provide information on gene expression. Finally, we speculate on future directions for this topic.